KEGIATAN EKONOMI BASIS SEBAGAI PENENTU EKSISTENSI BADAN USAHA MILIK DESA ( BUMDes ) DESA BADRAIN KECAMATAN NARMADA KABUPATEN LOMBOK BARAT. - PUTU KARISMAWAN; SUJADI SUJADI (GANEC SWARA, 2022)
Village-Owned Enterprises (BUMDes) are a new approach in an effort to improve the village economy based on the needs and potential of the village. Through this approach BUMDes is expected to be able to stimulate, facilitate and protect the economic activities of rural communities. This role is expected to be sustainable in the long term. Theoretically, the sustainability of an activity is determined by basic activities, namely activities that have a local economic strength base, are able to absorb labor and have competitiveness. Through a qualitative research approach, it was found that the management of BUMDes in Badrain Village has been running well, in the sense that it is able to help empower the community's economy, and can create jobs for the community. In addition, the Savings and Loans Business Unit BUMDes Desa Badrain plays a role in increasing community income by providing capital assistance to develop businesses owned/open new businesses. Furthermore, the BUMDes of Badrain Village has been able to provide PADes to the village. In carrying out its role in realizing the aims and objectives of the establishment of BUMDes, there are several obstacles faced by BUMDes in Badrain Village, both internal and external constraints, internal constraints occur, namely limited capital, high market competition, and the quality of human resources is still lacking.